Internationalization of domestic law in the context of legal positions of the Russian Constitutional Court and the Russian Supreme Court - E. S. Anichkin; A. A. Vasiliev; N. D. Usvyat (Правоприменение)
The article is aimed at identifying legal positions on the relationship between international and domestic Russian law in the decisions of Russian Constitutional Court and Russian Supreme Court.The purpose of the article is to confirm or disprove hypothesis that the practice of Russian Constitutional Court and Russian Supreme Court significantly changed the content of norm of Russian Constitution that recognizes generally recognized principles and norms of international law and international treaties as part of the Russian legal system.The methodological basis of the study was formed by both general scientific methods (dialectical, analysis and synthesis, induction and deduction) and special methods (synergistic, systemic-structural and formal-legal).The main results, scope of application. The main body of the article covers three interrelated issues. Firstly, the problems of interpretation of Pt. 4 of Art. 15 of the Russian Constitution. These problems are summarized to the ratio of the categories “generally recognized principles of international law” and “generally recognized norms of international law”, to possible contradictions between the current international treaty with the participation of Russia and the provisions of the Russian Constitution as well as to exceptions from the priority of international treaties over the domestic law of Russia. Five such exceptions are highlighted: the unconditional primacy of the Russian Constitution; domination of an international treaty only in the event of a conflict of its norms with the internal law of Russia; the presence in an international treaty of dispositive norms that are inferior to domestic law; taking into account the level of legal force when determining the correlation of an international treaty with the sources of national Russian law; implementation of an international treaty as self-executing or non-self-executing, when the priority of the latter directly depends on the adoption of an appropriate normative act of domestic law. Secondly, the system of legal positions of the Russian Constitutional Court on the relationship between international and domestic law and their target mission is considered. The legal positions on the issue under study are divided into two groups - on the interaction of international treaties with the domestic law of Russia and on the assessment of the prospects for the incorporation of the legal positions of the European Court of Human Rights into Russian legal system and the limits of its jurisdiction. The consolidating basis of all judicial legal positions is the unconditional priority of the Russian Constitution, the need to differentiate the normative content of an international treaty with the participation of the Russian Federation and acts of official interpretation by the authorized body of its norms, as well as the desire to preserve the constitutional identity of Russia. Thirdly, the subject of reflection was the limits of the internationalization of domestic law.Conclusions. There is an obstacle to the further internationalization of domestic law. It is the presence of spheres of public and state life that cannot and should not be included in the subject of international legal regulation and are subject exclusively to domestic legal impact. In addition, the framework of internationalization is due to the conflict with the state sovereignty of Russia and the desire to ensure the inviolability of the foundations of the constitutional order and national interests, and to ensure the country's constitutional identity.